Design and socialization of elderly-friendly hydraulic toilets for Elderly Shelter PCA Dau, Malang - Iis Siti Aisyah; Dini Kurniawati; Nur Hasanah; Moch. Syamsul Ma’arif (Journal of Community Service and Empowerment, 2024)
The spirit of improving the welfare of the elderly is the concern of Amal Usaha Aisyiyah, an autonomous organization under Muhammadiyah by establishing a Shelter for the Elderly in the Dau area, under the management of the Aisyiyah Dau Branch Leadership. One thing that is a serious problem is the need for infrastructure that supports the ease of movement of the elderly. It is common knowledge that the elderly's movements slow down and their motor skills are greatly reduced due to physical factors and age. This is what causes them to fall easily and get injured. And the majority of falls occur in the bathroom, in addition to wet conditions that can cause slipping, also because the toilet is not suitable, or is not friendly to the elderly. This community service is aimed at creating a special toilet design that provides convenience and safety when used. The method applied is by conducting anthropometric observations, interviews with elderly users and administrators and caregivers, conducting design calculations, fabrication followed by product testing and socialization to users. Finally, this community service succeeded in building an elderly-friendly hydraulic toilet with special specifications and has been given to the Shelter for the Elderly. The handover of the product was carried out simultaneously with testing and socialization. This product is expected to increase comfort for the elderly and reduce the occurrence of accidents involving falls in the bathroom.